The holocaust a history of courage and resistance - Stadtler, Bea; Martin, David Stone (New York Behrman House, 1974)
Describes the experiences of Jews in Germany and other European countries during the twelve years of the Third Reich when more than six million of their number were systematically destroyed.
Edition for 1973 published under title: The test.
Keywords: Holocaust, Jewish (1939-1945) -- Juvenile literature; Holocaust, Jewish (1939-1945); Jewish religious education -- Textbooks for children; World War, 1939-1945 -- Jewish resistance; World War, 1939-1945 -- Underground movements, Jewish -- Juvenile literature